Upaya Guru Mengatasi Kesulitan Siswa Belajar Matematika Pada Materi Pecahan Di Kelas VII SMP Negeri 7 Padangsidimpuan - Nasution, Rika Annum; Rangkuti, Ahmad Nizar; Hilda, Lelya (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2019)
The purpose of the efforts of teachers to overcome student learning difficulties in order to find out the efforts made by teachers to overcome the difficulties of students learning mathematics in fractions in class VII SMP Negeri 7 Padangsidimpuan. This research is a classroom action research conducted using the cycle method. The instruments used are observation and test in the form of essays.Based on the results of the study, it was found that the students' initial abilities in the fraction material through the learning model, this can be seen and the increase in the results of the average initial test scores of all students was 65 and the number of students who passed 5 students with a percentage of 20% and 25 students. In the Â first cycle test meeting 1 with an average score of all students, namely 69.08 and the number of students who graduated 13 students with a percentage of 52% and 25 students. In the second session of the first test session, the average of all students was 72.6 and the number of students who graduated was 15 students with a percentage of 60% and 25 students. While the second cycle of meeting 1 test with an average value of all students is 78.2 and the number of students who passed 19 students with a percentage of 76% and 25 students. In the 2nd meeting cycle II test with an average value of all students, namely 82 and the number of students who graduated 21 students with a percentage of 84% and 25 students. Based on the percentage of graduation students have reached the desired level, this study was stopped until the second meeting of the cycle II.